Geodynamics Research International Bulletin (GRIB) - Independiente (Independiente, 2026)
Geodynamics Research International Bulletin (GRIB) is a quarterly peer-reviewed scientific journal published by Gemsco, which broadly covers Earth and planetary sciences, including geology, tectonics, geomorphology, geophysics, geological hazards, geodynamics and geodesy. The editors-in-chief are Professor Bahram Akashe (Tehran University, Iran), Dr. Mehdi Zare (Tehran University, Iran), Dr. Lidong Dai (Yale University, USA) and Dr. Mohammad Aryamanesh (Payam Noor University, Iran).
Keywords: Geodinámica; Ciencias de la Tierra; Revistas depredadoras; Predatory journals